Ticks in periurban areas from the municipalities of La Costa and General Lavalle : A preliminary study - Soba, Marina G. (2022)
In Argentina, spotted fever rickettsiosis caused by Rickettsia parkeri is a zoonotic disease with tick Amblyomma triste as its principal vector. The presence of this tick species restricts to areas of La Plata hydrographic basin in the province of Buenos Aires. The adult stages of A. triste can parasitize dogs and cats. The aim of this study is to detect the presence of A. triste in dogs and humans from municipalities of General Lavalle and La Costa (Buenos Aires).